El vino como alimento y medicina en la sociedad romana - Real Torres, Carolina (1992)
Roman native medicine had a strong tradition. The Romans thought physicians did not exist in their early history, but supposed the Romans of old practised medicine in general terms. Early Roman medical concepts were enclosed in the common religion of countryside. The Romans agronomists make the farm the centre of bis attention, where thepater famihas was the dispenser of medical remedies of bis household. Characteristic of early Roman medicine is a reliance upon remedies, in which, as we reed the writings of the Ancients, we find various kinds of wines shared in those.
Keywords: Vinos; Alimentación; Medicina; Roma